2002
DOI: 10.1177/159101990200800103
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Anomalies and the Risk of Multiple Aneurysms Development and Bleeding

Abstract: The pathogenesis of aneurysmal subarachnoid hemorrhage is still debated and the prognosis remains severe, especially in multiple aneurysms, where the therapeutic management is complex. The aim of this study was to look for vascular anomalies and assess their relationship with aneurysm formation and bleeding in patients with multiple intracranial aneurysms. A prospective angiographical review was performed on 141 patients with multiple intracranial aneurysms seen from 1992 to 2000. Three hundred and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The results corroborate previous findings that showed that patients with a single AA had a higher risk of subarachnoid hemorrhage than did patients harboring multiple AAs. 18 The total number of intradural saccular AAs in this patient cohort was 806, among which 320 were ruptured and treated, indicating that the majority of this type of AA do not bleed, at least within the observation time frame presented here.…”
Section: Demographicsmentioning
confidence: 66%
“…The results corroborate previous findings that showed that patients with a single AA had a higher risk of subarachnoid hemorrhage than did patients harboring multiple AAs. 18 The total number of intradural saccular AAs in this patient cohort was 806, among which 320 were ruptured and treated, indicating that the majority of this type of AA do not bleed, at least within the observation time frame presented here.…”
Section: Demographicsmentioning
confidence: 66%
“…A variation of the circle of Willis was regarded as congenital abnormalities (5,22). Arteries with external diameter less than 1 mm and communicating arteries smaller than 0.5 mm were accepted as "hypoplastic" and the absence of the artery as "aplastic" (1,6,20,28).…”
Section: █ Materials and Methodsmentioning
confidence: 99%
“…arteriovenous malformation or cerebrovascular occlusive disease by changing the blood-flow pattern and increasing hemodynamic stress (3,4,7,12,13,15,23,26,29). There are some reports that have investigated the relationship between variations and aneurysm localization in cadaveric (12,20,28) and clinical studies (14,18,22,31).…”
mentioning
confidence: 99%
“…In other reports, PICA with an extradural origin is regarded as a risk factor for aneurysmal formation or occlusion. 9,11,16,24,27,29 Some authors argue that extradural PICAs are vulnerable to dissection because they tend to be forcefully stretched by neck motions or chiropractic procedures. 23,24,27 When encountering patients with subarachnoid hemorrhage in the posterior fossa with an unknown etiology, carefully consider involvement of an extradural PICA.…”
Section: Discussionmentioning
confidence: 99%